2013
DOI: 10.1016/j.immuni.2013.06.013
|View full text |Cite
|
Sign up to set email alerts
|

The Autoimmunity-Associated Gene PTPN22 Potentiates Toll-like Receptor-Driven, Type 1 Interferon-Dependent Immunity

Abstract: SUMMARY Immune cells sense microbial products through Toll-like receptors (TLR), which trigger host defense responses including type 1 interferons (IFNs) secretion. A coding polymorphism in the protein tyrosine phosphatase nonreceptor type 22 (PTPN22) gene is a susceptibility allele for human autoimmune and infectious disease. We report that Ptpn22 selectively regulated type 1 IFN production after TLR engagement in myeloid cells. Ptpn22 promoted host antiviral responses and was critical for TLR agonist-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
314
4
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 181 publications
(330 citation statements)
references
References 48 publications
(74 reference statements)
10
314
4
2
Order By: Relevance
“…Thus far, two nonphosphatase activities of PTPN22 have been identified: suppressing citrullination and promoting LPS-induced production of type I interferon by myeloid cells (29,41). The observation that the abnormal Th2/Th17 cytokine profile of ARI PBMCs was partly normalized by a pan-PAD inhibitor and was recapitulated by overexpression of PADs strongly suggests that failure to suppress citrullination, but not failure to produce type I interferon, is the cause of the abnormal cytokine profile.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus far, two nonphosphatase activities of PTPN22 have been identified: suppressing citrullination and promoting LPS-induced production of type I interferon by myeloid cells (29,41). The observation that the abnormal Th2/Th17 cytokine profile of ARI PBMCs was partly normalized by a pan-PAD inhibitor and was recapitulated by overexpression of PADs strongly suggests that failure to suppress citrullination, but not failure to produce type I interferon, is the cause of the abnormal cytokine profile.…”
Section: Discussionmentioning
confidence: 99%
“…However, the reciprocal changes in Th2 and Th17 cytokines observed in ARI PBMCs cannot be explained by stronger activation signals in T cells. In addition to acting as a phosphatase, PTPN22 also has nonphosphatase activities, including suppressing citrullination and promoting TLR-induced expression of type I interferon (29,41). To determine if PTPN22 shaped the phenotype of ARI PBMCs through its phosphatase or nonphosphatase activity, we also expressed W620-PTPN22 or a catalytic dead PTPN22 (CD-PTPN22) in ARI PBMCs.…”
Section: Hypercitrullination In Pbmcs Of Healthy Aris the Observatiomentioning
confidence: 99%
See 1 more Smart Citation
“…However, the phosphorylation modification of key proteins in PRRs signaling has not been fully elucidated. Protein tyrosine phosphatases (PTPs), which dephosphorylate tyrosine residues of target substrates (15,16), have been reported to be involved in the regulation of innate immune responses, such as Src homology region 2 domain-containing phosphatase-1 (17), Src homology region 2 domain-containing phosphatase-2 (18), PTPN22 (19), PTP with proline-glutamine-serine-threonine-rich motifs (20), PTP1B (21), and so on. However, the PTPs identified to be PRRs regulators possessed broadly regulatory effects and that limited their potential implication for immunotherapy.…”
mentioning
confidence: 99%
“…Although recent evidence has demonstrated that Ptpn22 controls germinal center and Ab responses by modulating the activity of T follicular helper cells (15), several studies also suggest a direct role of Ptpn22 in B cell function (16,17). In addition to its role in cells of the lymphoid lineage, Ptpn22 has also been shown to facilitate type I IFN responses in myeloid cells after TLR engagement, further establishing its diverse and important role in the regulation of the immune system (18).…”
mentioning
confidence: 99%